The influence of eco-initiative behaviors on green warehousing adoption towards sustainable logistics practices / Mohd Rizaimy Shaharudin ... [et al.] - Shaharudin, Mohd Rizaimy; Akbar, Jamaludin; Hassam, Siti Fairuza; Abdullah, Dahlan; Jamal, Anis Hafinas (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
Today, many companies are emphasizing on the importance of employees engagement in the ecological practices and have incorporated this in their policies and procedures. This happens as a result of the companies’ participation in the green practices to meet the environmental strategy, stakeholders’ demand as well as the need to comply with the stringent environmental law and legislation. A review of the literature reveals that the study on the influence of organizational behavior on the green practices especially in the warehouse management area is still scanty. Thus, the aim of this study is to determine the relationship between the employees’ eco-initiative behaviors on the green warehouse adoption and their impact on the sustainable green logistic practices. The study utilized quantitative approach and employed a research model that was developed from the literature by analyzing 100 respondents of the warehouse operators across several states in Peninsular Malaysia. SPSS software was used to analyze the data which were collected based on the cross-sectional study. Purposive sampling technique has been used to select the sample of study. The results signified that eco-initiative behaviors have a direct impact on green warehouse adoption. Subsequently green warehouse adoption does affect the sustainable green logistic of the firm. The eco-initiative behaviors and support from the warehouse employees can impact the adoption of green warehouse and this would eventually leads to sustainable environmental protection from the risk of waste generation across the supply chain channel. The outcome of the study has also added a new field of knowledge and provided new insight in the green practices of the warehousing sectors. It significantly assists the theory building of a limited field in the warehouse operations. In practical terms, it is important for the warehouse operators to always enhance and maintain the environmental culture in the company so as to increase the green warehouse adoption and sustainable logistics practices in their organizations.